ANALISIS KEMAMPUAN BERPIKIR KREATIF, BERPIKIR KRITIS MATEMATIK SISWA SMK PADA MATERI SPLDV - Fany Afriliany Maya; Ika Kartika Sari; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This research is an qualitative descriptive research which aim to know high or low the ability of mathematical creative thinking and mathematical critical thinking on system of two variable equations. The subject of this research were 30 students at 10th grade in one of the vocational high school in Galanggang Village. Data collection is done by giving 5 questions  for each creative thinking ability and critical thinking ability to the students. Data obtained are then processed and analyzed later will concluded that mathematical creative thinking ability and mathematical critical thinking ability in one of the vocational high school in Galanggang Village is still low. This conclusion is based on results the average of the percentage obtained from the five indicators of creative thinking ability is 21.81% and from critical thinking ability is 43.44%.